2019
DOI: 10.1002/mar.21204
|View full text |Cite
|
Sign up to set email alerts
|

Feelings and functionality in social networking communities: A regulatory focus perspective

Abstract: A sense of community is vital to the sustainability of both face‐to‐face and virtual communities. In this study, we use a mixed methods design to study the motivations that lead to satisfaction in a social media network. In Study 1, we semantically analyze the qualitative comments from a survey regarding the reasons for using social networks (n = 237). Consistent with the literature, the results identify two categories of underlying motivations—hedonic (feelings) and utilitarian (functionality). With these res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 62 publications
(82 reference statements)
0
26
0
Order By: Relevance
“…To explore the qualitative tweets corresponding with #MeToo posts from respondents, we utilized Leximancer (http://www.leximancer.com), a semantic analysis tool designed to identify themes and concepts as a series of associations and links (Smith, 2007). This technique has been used to explore various types of qualitative comments (e.g., Krishen et al, 2014, 2019; Petrescu & Kachen, 2019). Themes are shown as large shaded circles and represent higher‐order clusters of semantically connected groups of concepts, which are shown as smaller shaded circles.…”
Section: Methodology: the Case Of Academia And Corporationsmentioning
confidence: 99%
“…To explore the qualitative tweets corresponding with #MeToo posts from respondents, we utilized Leximancer (http://www.leximancer.com), a semantic analysis tool designed to identify themes and concepts as a series of associations and links (Smith, 2007). This technique has been used to explore various types of qualitative comments (e.g., Krishen et al, 2014, 2019; Petrescu & Kachen, 2019). Themes are shown as large shaded circles and represent higher‐order clusters of semantically connected groups of concepts, which are shown as smaller shaded circles.…”
Section: Methodology: the Case Of Academia And Corporationsmentioning
confidence: 99%
“…Our qualitative inquiry began with an exploratory analysis of the data set to delineate content utilizing social media from content proposing possible solutions to the problem of IWT. Since the focus of this paper is to explore the rhetorical strategy employed in various forms of messaging, we chose Leximancer as a method of analysis (c.f., Krishen, Berezan, & Raab, 2019). Leximancer is an unguided semantic analysis tool that uses a machine learning technique to identify relevant ideas (Smith, 2007).…”
Section: Qualitative Netnography Studymentioning
confidence: 99%
“…More and more scholars have begun to explore the value of emotional information in the context of social media. For instance, Krishen, Berezan, and Raab (2019) has found that, in a social network, a sense of belonging and emotional connection are key hedonic elements and are more relevant for promotion-focused individuals. But, for prevention-focused individuals, the utilitarian and functional aspects of interactivity(influence) and innovativeness(risk) are more important factors in influencing satisfaction with a social network.…”
Section: Emotion and Cognitionmentioning
confidence: 99%